Global Snapshot - Garg, Vijay K (Concurrent and Distributed Computing in Java, 2005)
This Chapter includes the following topics: Introduction Chandy and Lamport's Global Snapshot Algorithm Global Snapshots for non-FIFO Channels Channel Recording by the Sender Application: Checkpointing a Distributed Application Problems Bibliographic Remarks